2001
DOI: 10.1128/iai.69.1.170-176.2001
|View full text |Cite
|
Sign up to set email alerts
|

Silencing and Reactivation of Urease in Yersinia pestis Is Determined by One G Residue at a Specific Position in the ureD Gene

Abstract: Yersinia pestis, the plague agent, is a naturally nonureolytic microorganism, while all other Yersinia species display a potent urease activity. In this report we demonstrate that Y. pestis harbors a complete urease locus composed of three structural (ureABC) and four accessory (ureEFGD) genes. Absence of ureolytic activity is due to the presence of one additional G residue in a poly(G) stretch, which introduces a premature stop codon in ureD. The presence of the same additional G in eight other Y. pestis isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…Production of urease contributes to the pathogenicity Y. pseudotuberculosis as it is necessary for oral transmission (6). A premature stop codon introduced in the ureD gene of the ureABCEFGD operon results in the absence of ureolytic activity in Y. pestis, but does not modify the pathogenicity of Y. pestis in the mouse experimental model (30). Transcription of the whole ure operon was upregulated at 26 C (Table 3).…”
Section: Other Virulence Determinantsmentioning
confidence: 94%
“…Production of urease contributes to the pathogenicity Y. pseudotuberculosis as it is necessary for oral transmission (6). A premature stop codon introduced in the ureD gene of the ureABCEFGD operon results in the absence of ureolytic activity in Y. pestis, but does not modify the pathogenicity of Y. pestis in the mouse experimental model (30). Transcription of the whole ure operon was upregulated at 26 C (Table 3).…”
Section: Other Virulence Determinantsmentioning
confidence: 94%
“…Nowadays, in Madagascar, there are observations of pneumonic plague cases among persons attending ritual excavation of plague corpses in the absence of direct contact with the dead (Harilanto Razafindrazaka, personal communication). It has been previously suggested that Y. pestis urease may play a role in environmental adaptation (Sebbane et al, 2001). Indeed, unlike other Yersinia species, Y. pestis lacks urease activity due to a frameshift mutation (Sebbane et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A similar process has been demonstrated in Y. pestis. The organism is characteristically urease negative but activity can be restored in vitro by the spontaneous deletion of a single base pair in a homopolymeric tract in ureD 22 . This type of reversible mutation would reduce the metabolic burden of producing proteins unnecessary to Y. pestis in its new¯ea/mammal life cycle yet still allow the potential to express these should a subsequent need arise.…”
mentioning
confidence: 99%